ANALISIS PERILAKU KONSUMEN DIEVHA CAFÉ DI KECAMATAN SUMBER JAYA KABUPATEN LAMPUNG BARAT - Muslimah, Putri Ayu; Indriani, Yaktiworo; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This research aims to analyze decision making, attitude, satisfaction and customer loyalty of Dievha Café in Sumber Jaya District, West Lampung Regency.  The method used in this research is a survey method by conducting direct interviews using questionnaires to 60 respondents who have made at least 2 purchases during the last 3 months and are at least 17 years old.  Data collection was carried out in January-February 2023.  The Data are analyzed descriptively using Fishbein's multiattributes, Customer Satisfaction Index (CSI), and loyalty pyramid.  The results of this research showed that the first reason consumers buying were because they wanted to try the products, they got the location information from their friends and their main consideration for purchases was the taste.  The consumers would switch to other menus when the product was run out and they decided to buy themselves on purpose.  All of the consumers were interested in repurchases and 63.33 percent of them were satisfied.  From the analysis of Fishbein’s  multiattributes showed the score was 136.95 or in a good category.  The most preferred attribute was taste with score of 18.13, followed by the location attribute and the employee service attribute.  The level of consumer satisfaction on Dievha Café products obtained a value of 82.77 percent or categorized as very satisfied with the highest score attribute was the taste.  The level of consumer loyalty to Dievha Café based on the loyalty pyramid analysis was in the satisfied buyer category (73.33%), followed by liking the brand (71.67%), committed buyer (70.00%), switcher buyer (40.00%), and habitual buyer (36.67%).Keywords: coffee shop, consumer attitudes, decisions making, loyalty, satisfaction.